PENGARUH WORKLOAD DAN STRESS KERJA TERHADAP KINERJA KARYAWAN DENGAN CYBERLOAFING SEBAGAI MEDIASI - Assidiqi, Muhammad Iqbal Fatur; Suryosukmono, Gerry (FEB Universitas Sam Ratulangi Manado, 2023)
Employee performance is an important factor for measuring the success of a company or organization. This research aims to measure the effect of workload and work stress on employee performance with cyberloafing as mediation. The research sample consisted of 117 employees who worked at the Manpower and Transmigration Service of Bengkulu City. The instrument used in this research is a structured questionnaire that measures workload levels, work stress, employee performance and cyberloafing. The data that has been collected will be analyzed using the SmartPLS3 application. The research results show that workload, work stress and cyberloafing influence employee performance both directly and indirectly. The conclusions of this research provide a greater understanding of employee performance which is influenced by factors such as workload, work stress and cyberloafing and how all of this should have a positive impact on improving performance.